DOUBLE BURDEN STRESS IN WOMEN AND THE ROLE OF PSYCHO-RELIGIOUS WORSHIP IN ALLEVIATING IT - Putra, Fahmi Mandala; Ismah, Zata; Syahfitri, Rizky Indah; Nasution, Citra Cahyati; Putri, Az-zahra Atika; Amirah, Fitria; Helmi, Tri Amelia Rahmitha (Folia Medica Indonesiana, 2025)
It has been recognized that women are twice as likely to experience depression compared to men. In addition to biological vulnerability, there is also a combined effect of bearing the burden of household responsibilities while contributing financially through employment. One coping strategy that helps women endure these challenges is meditation, which in Islam includes the practice of dhikr (remembrance of God). This study aims to analyze the phenomenon of double burden stress in women and how psychoreligious practices can help reduce stress levels. The study employed a prospective cohort design, tracking the respondents' dhikr habits over a 21-day period. On the final day, general stress levels and stress related to their professional roles were measured. The study involved 69 women participants aged 17 and above, comprising housewives as well as women who held dual roles as both teachers and students. Stress levels were assessed using the DASS-42 instrument. Respondents recorded the number of times they missed the istighfar recitation at specific times of the day on a control card. Findings indicated that women who are mothers and simultaneously hold dual roles as teachers and students are more vulnerable to stress. Further correlation tests revealed that missing istighfar after the Fajr prayer, before the Asr prayer, and after the Isha prayer was associated with increased stress levels. The predictive model showed that collectively missing istighfar at these three times (after Fajr, throughout daily activities, and the total missed times) significantly increased the likelihood of stress among women. The study concludes that women who have dual roles as mothers and teachers or students are the most vulnerable group to stress. Moreover, the more frequently istighfar is neglected at the recommended times, the higher the stress levels experienced by women.